(3GdPNjQI aj eMGSf Cgd GdLRjQIs - (3Ydj Hf HSGe GdTfJQjfj GdCfOdSj, CHh GdMSf,J (B542 (3g` s
(3ChdgG (B:s
(3aUd aj PcQ GdCYjGf GdeTGgjQ ef CQHGH UfGYI GdefXhe hGdefKhQ HMVQI CTHjdjI hfhGMjgG s
(3BNQgG (B:s
(3de jQVg YQoV GdOfjG aLGO Hg hVf HGdCcQejf GdYQV hGdOjf s
(3GdbSe GdKGfj ef fSNI KGfjIs
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B266 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B43s
Keywords: (3GdJGQjNs